Upaya Pengendalian Parasit untuk Meningkatkan Produktivitas Sapi pada Usaha Peternakan Sapi di Distrik Tanah Miring Kabupaten Merauke - Salamony, Syetiel Maya; Prasetya, Muhammad Novan; Daoed, Denvy Meidian; Hutabarat, Desmina Kristiani; Gebze, Yolanda; Praptiwi, Irene Ike; Lesik, Maria Magdalena Nay Nadu; Nurcholis, Nurcholis; Irianto, Apri (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The majority of the population of Tanah Miring District, Merauke Regency work as farmers and livestock breeders by utilizing agricultural waste as animal feed. The livestock pattern that is managed traditionally and has not been controlled for health, has resulted in a decrease in the productivity of livestock businesses which results in sudden livestock deaths. The implementation method includes two stages, namely socialization and implementation of activities consisting of two activities, namely physical activities and non-physical activities. The results of the community service, namely socialization, were carried out in two places, namely in the local government and at the Merauke Regency Food Security, Animal Husbandry and Animal Health Service, physical activities in the form of cage sanitation and provision of multivitamins and medicines to livestock farmers, while non-physical activities in the form of counseling on the prevention and control of diseases caused by parasites. This activity received a positive response from the community so that it could be carried out well and successfully helped reduce the mosquito population in the cage environment, increase the immunity of livestock from disease attacks and increase the productivity of cattle farming businesses in Merauke Regency.